2014
DOI: 10.1159/000369183
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Analysis and Chromosomal Distribution of Repetitive DNA Sequences of <b><i>Cucumis metuliferus</i></b> Using Fluorescence in situ Hybridization

Abstract: Cucumis metuliferus (2n = 24) is a cultivated species of the Cucumis genus which is a potential genetic resource for Cucumis crops. Although some cytogenetic research has been reported, there is no study of karyotyping in this species. Here, we used 4′,6-diamidino-2-phenylindole and chromomycin A3 staining to identify 12 pairs of chromosomes in early-metaphase cells. Fluorescence in situ hybridization revealed the chromosomal distribution patterns of the 5S and 45S ribosomal DNA (rDNA) genes, telomeres, and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…In another phylogenetic study, it was suggested that C. metuliferus may be derived from the African Cucumis species, and thus may be a putative diploid ancestral species of the C. heptadactylus group [Sebastian et al, 2010]. The 45S rDNA and 5S rDNA of C. metuliferus was mapped previously on chromosomes 11 and 12 [Yagi et al, 2014]. In our study, chromosomes 11 and 12 of C. metuliferus were found to be rch type I and II, respectively.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In another phylogenetic study, it was suggested that C. metuliferus may be derived from the African Cucumis species, and thus may be a putative diploid ancestral species of the C. heptadactylus group [Sebastian et al, 2010]. The 45S rDNA and 5S rDNA of C. metuliferus was mapped previously on chromosomes 11 and 12 [Yagi et al, 2014]. In our study, chromosomes 11 and 12 of C. metuliferus were found to be rch type I and II, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…The probes were directly labeled with tetramethyl-rhodamine-5-dUTP (red) (Roche Diagnostics, Mannheim, Germany) using a nick translation kit (Roche Diagnostics). The chromosomal preparation and FISH methods were performed following Yagi et al [2014]. After checking the locations of the signals, blended probes were used for signal detection.…”
Section: Chromosomal Preparation and Fishmentioning
confidence: 99%
“…In Cucumis, studies involving molecular cytogenetics were mainly focused on important cultivated crops (e.g., cucumbers, melons) (Chen et al 1998;Han et al 2008;Liu et al 2010). Few relevant studies have been reported concerning the genome organization and chromosomal structure of wild species, except for some concerning chromosome morphology and karyotype (Chen et al 1999;Zhao et al 2011;Yagi et al 2014Yagi et al , 2015. Most wild species of Cucumis have small chromosomes, which makes traditional cytogenetics methods, like banding, not suitable for Cucumis chromosome analysis (difficult to stain).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome painting clones enable ancestral genome recognition in allopolyploid species. Zhang et al [ 45 ] identified sequences that distinguish the three genomes of Triticum aestivum , and in Cucumis metuliferus a species-specific repetitive sequence (pMetSat) has been identified by Yagi et al [ 46 ]. In our study, we observed a hybridization signal of the chromosome-like painting clone L16 Fp04 only in F .…”
Section: Discussionmentioning
confidence: 99%